Three daphnane diterpenoids from Trigonostemon xyphophylloides. (March 2015) - Yang, Biao; Meng, Zhaoqing; Li, Zhaoliang; Sun, Lin; Hu, Yumei; Wang, Zhenzhong; Ding, Gang; Xiao, Wei; Han, Changri
Graphical abstract: Highlights: Trigoxyphins U–W (1 –3 ), together with two known compounds were isolated from Trigonostemon xyphophylloides . The structures were elucidated by extensive analysis of the spectroscopic data. Compound3 showed modest cytotoxicity against BEL-7402, SPCA-1 and SGC-7901 cancer cell lines. Abstract: Three daphnane diterpenoid trigoxyphins U–W (1 –3 ), together with two known daphnane diterpenoids (4 and5 ) were isolated from Trigonostemon xyphophylloides . Their structures were elucidated by spectroscopic analysis. Compound3 showed modest cytotoxicity against BEL-7402, SPCA-1 and SGC-7901 cancer cell lines.